A Modified Method for Studying Behavioral Paradox of Antioxidants and Their Disproportionate Competitive Kinetic Effect to Scavenge the Peroxyl Radical Formation - Nusrat Masood; Kaneez Fatima; Suaib Luqman (The Scientific World Journal)
We have described a modified method for evaluating inhibitor of peroxyl radicals, a well-recognized and -documented radical involved in cancer initiation and promotion as well as diseases related to oxidative stress and ageing. We are reporting hydrophilic and lipophilic as well as natural and synthetic forms of antioxidants revealing a diversified behaviour to peroxyl radical in a dose-dependent manner (1 nM–10 μM). A simple kinetic model for the competitive oxidation of an indicator molecule (ABTS) and a various antioxidant by a radical (ROO•) is described. The influences of both the concentration of antioxidant and duration of reaction (70 min) on the inhibition of the radical cation absorption are taken into account while determining the activity. The induction time of the reaction was also proposed as a parameter enabling determination of antioxidant content by optimizing and introducing other kinetic parameters in 96-well plate assays. The test evidently improves the original PRTC (peroxyl radical trapping capacity) assay in terms of the amount of chemical used, simultaneous tracking, that is, the generation of the radical taking place continually and the kinetic reduction technique (area under curve, peak value, slope, and Vmax).